Kindlich experimentelles Komponieren wider die Schablonen: Mozarts „Londoner Skizzenbuch“, London und Chelsea, Juli/August 1764 (KV 15a–ss) - Sühring, Peter (Die Musikforschung, 2023)
The compositional experiments and exercises written by eight-year-old Mozart in London in 1764 show original musical ideas which he went on to pursue later, making him an anti-classic par excellence. His London sketchbook was created in a sphere of intense encounters with old and new models of vocal and instrumental music and had a long-lasting effect. The special circumstances surrounding its creation – Leopold Mozart was ill and could not assist Wolfgang in editing the music – make the notebook appear as a collection of raw versions of piano pieces, which, however, go beyond compositions intended for a keyboard instrument. Previous editions of the London sketchbook, especially those produced by Wolfgang Plath for the Neue Mozart-Ausgabe, did not reproduce the 43 piano pieces authentically, but rather marred them with emendations. Two examples, an alleged “Siciliano” and an alleged “Prelude”, are used to hold Mozart’s musical texts against these untenable assessments